Coiling-Up Space Metasurface for High-Efficient and Wide-angle Acoustic Wavefront Steering - Chen, Shuang; Fan, Yuancheng; Yang, Fan; Sun, Kangyao; Fu, Quanhong; Zheng, Jianbang; Zhang, Fuli (Frontiers in Materials, 2021)
The recent advent of acoustic metasurface displays tremendous potential with their unique and flexible capabilities of wavefront manipulations. In this paper, we propose a new acoustic metasurface, i.e. metagrating made of binary coilong-up space structures to coherently control the acoustic wavefront steering. The acoustic wave steering is based on in-plane coherent modulation of waves in different diffraction channels. The acoustic metagrating structure with a subwavelength thickness is realized with 3D-printed two coiling-up space metaunits. By adjusting structural parameters of the metaunits, the -1st order diffraction mode can be retained, and the rest of the diffraction orders are eliminated as much as possible through destructive interference, forming a high-efficiency anomalous reflection in the scattering field. The anomalous reflection performance of the designed metagrating is achieved over a wide range of incident angles with high-efficiency.